Catalyst diffusion electrode and preparation method and application thereof
By covering the carbide pre-plating layer on the surface of the diffusion material of the PEM electrolytic cell and depositing precious metal catalysts, the problems of leaching and high loading of precious metal elements of the traditional catalyst-coated electrode are solved, and higher binding strength and lower loading are achieved, which promotes the industrialization of PEM electrolytic cell.
Patent Information
- Application Number
- CN202411777421.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-04
AI Technical Summary
Traditional catalyst-coated electrodes have problems with leaching precious metal elements in high corrosion and high potential environments, resulting in a decay of the service life of the electrode materials, and the loading of noble metal elements leads to excessive manufacturing costs, which hinders the advancement of the industrialization of PEM electrolytic cells.
By covering the carbide pre-plating layer on the surface of the diffusion material and depositing precious metals or their oxide catalysts on the surface, the strong binding energy of carbon elements and precious metal elements is used to form a strong interaction force, enhance the binding strength between the catalyst and the substrate, and optimize the electronic structure of the catalyst to reduce the load of precious metal elements.
It significantly reduces the leaching rate and loading of precious metal elements, improves the bonding strength between the catalyst and the substrate, extends the service life of the electrode material, reduces the manufacturing cost, and promotes the industrialization of PEM electrolytic cells.
Smart Images

Figure CN119553313A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogen production by electrolysis of water, and specifically relates to a catalyst diffusion electrode and a preparation method and application thereof. Background Art
[0002] Hydrogen energy has the advantages of high combustion calorific value, high energy density, no pollution in terminal use, storability and renewability, etc. It is praised by the International Energy Agency as "the core of the future energy architecture". Proton exchange membrane (PEM) water electrolysis technology is one of the core hydrogen production technologies to achieve a carbon-free energy cycle.
[0003] In a PEM electrolyzer, diffusion materials, catalysts and PEM are its core components. Among them, the catalyst, as the place where the water electrolysis reaction occurs, directly determines the performance of the entire electrolyzer. The cathode / anode side of the PEM water electrolysis usually faces a high corrosion and high potential environment. Precious metals or their oxides such as platinum and iridium oxide have been proven to be used as cathode / anode catalysts under these harsh conditions to ensure efficient and stable operation of the water electrolysis reaction. In actual use, the precious metal or its oxide catalyst usually needs to be further loaded on the surface of the substrate to prepare an electrode material. The traditional method of preparing electrode materials is to spray or coat the precious metal or its oxide catalyst on the surface of the PEM to prepare a catalyst-coated electrode.
[0004] However, the catalyst-coated electrodes prepared by the traditional electrode material preparation method still have the following problems:
[0005] Catalyst coated electrodes rely on a binder to bond precious metals or their oxide catalysts to the PEM surface. In the actual reaction process, the precious metal elements are often leached, resulting in a reduction in the service life of the electrode material. In addition, in order to ensure high current density operation under specific voltage conditions, catalyst coated electrodes usually require a high precious metal element loading during actual use, resulting in excessively high manufacturing costs for electrode materials.
[0006] The above problems have seriously hindered the advancement of PEM electrolyzer industrialization. Summary of the invention
[0007] In order to solve the above technical problems, the present invention provides a catalyst diffusion electrode and a preparation method and application thereof. Compared with the traditional catalyst coated electrode, the present invention loads the catalyst on the surface of the diffusion material through carbide, which has higher bonding strength. When achieving the same catalytic effect, the required loading amount of precious metal elements is significantly reduced.
[0008] The present invention is specifically implemented through the following technical solutions.
[0009] The present invention provides a catalyst diffusion electrode, including a diffusion material, a carbide pre-plating layer is sequentially deposited on the surface of the diffusion material, and a noble metal or its oxide catalyst is deposited on the surface of the carbide pre-plating layer. The carbon element in the carbide has a very strong binding energy with noble metal elements such as platinum, iridium and ruthenium. The present invention first covers a layer of carbide pre-plating layer on the surface of the diffusion material as a binding site for the noble metal or its oxide catalyst. When the noble metal or its oxide catalyst lands on the surface of the diffusion material, it will be anchored together with the carbide pre-plating layer on the surface of the diffusion material. This bonding method is different from the bonding method of the traditional catalyst film electrode that relies on bonding with a binder. It is a strong interaction force that can significantly enhance the bonding strength between the catalyst and the substrate. In addition, the carbide pre-plating layer introduced by the present invention can optimize the inherent electronic structure of the noble metal or its oxide catalyst, thereby improving its intrinsic activity, thereby significantly reducing the loading amount of the noble metal element.
[0010] Preferably, the carbide pre-plating layer is one or more of MoC, Mo2C, WC and W2C; the carbide pre-plating layer is in the form of a thin film with a thickness of 1 μm to 10 μm.
[0011] Preferably, the noble metal or its oxide catalyst is one or more of Pt, Ir, Ru, PtO, PtO2, IrO2, IrO3, Ir2O3, RuO2 and RuO4, and the noble metal or its oxide catalyst is in granular form with a particle size of 1nm to 10nm.
[0012] Preferably, the coverage of the noble metal or its oxide catalyst on the surface of the carbide pre-plating layer is 50% to 100%; the mass ratio of the noble metal or its oxide catalyst to the carbide pre-plating layer is 1% to 10%.
[0013] Preferably, the diffusion material is one or more of fiber sintered titanium felt and powder sintered titanium plate; the diffusion material has a thickness of 0.1 mm to 2.0 mm, a porosity of 20% to 80%, and an average particle size of 1 μm to 100 μm.
[0014] The present invention also provides a method for preparing the catalyst diffusion electrode, comprising the following steps:
[0015] A carbide pre-plating layer is prepared on the surface of the diffusion material by a vapor deposition method.
[0016] The noble metal or its oxide catalyst is prepared on the surface of a diffusion material covered with a carbide pre-plating layer by an electrochemical deposition method.
[0017] Traditional catalyst-coated electrode preparation methods such as spraying and coating methods must use a binder, which is a macroscopic-scale physical bonding material forming method. The vapor deposition method and electrochemical deposition method used in the present invention are a microscopic-scale in-situ growth material forming method, which is beneficial to promote atomic-scale chemical bonding between the catalyst and the substrate, thereby forming a strong interaction interface and regulating the loading amount of precious metal elements on the substrate surface.
[0018] Preferably, before preparing the carbide pre-plating layer, the diffusion material is also pretreated; the pretreatment includes acetone washing, ethanol washing, acid washing, water washing and drying in sequence.
[0019] Preferably, the vapor deposition method is physical vapor deposition or chemical vapor deposition.
[0020] Preferably, the method for preparing the carbide pre-plating layer comprises the following steps: using carbide as a source material, using a diffusion material as a substrate, controlling the vacuum degree and temperature of the chamber, and applying power to prepare the carbide pre-plating layer on the surface of the diffusion material.
[0021] Preferably, the electrochemical deposition method is an anodic oxidation method or a cathodic reduction method.
[0022] Preferably, the noble metal or its oxide catalyst is deposited on the surface of the carbide pre-plating layer by the following steps: using a diffusion material covered with a carbide pre-plating layer as a working electrode, using an aqueous solution of a noble metal salt, a complexing agent and a pH regulator as an electrolyte solution, applying a redox potential, and preparing a noble metal or its oxide catalyst on the surface of the diffusion material covered with a carbide pre-plating layer.
[0023] The present invention provides application of the catalyst diffusion electrode in PEM water electrolysis electrode materials.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The present invention provides a catalyst diffusion electrode, including a diffusion material and a carbide pre-plating layer and a noble metal or its oxide catalyst sequentially arranged on the surface of the diffusion material. Based on the fact that carbon elements have very strong binding energy with noble metal elements such as platinum, iridium and ruthenium, the present invention first covers the surface of the diffusion material with a carbide pre-plating layer as a binding site for the noble metal or its oxide catalyst. When the noble metal or its oxide catalyst lands on the surface of the diffusion material, it will be anchored together with the carbide pre-plating layer on the surface of the diffusion material. This bonding method is different from the bonding method of the traditional catalyst film electrode that relies on bonding with a binder. It is a strong interaction force that can significantly enhance the bonding strength between the catalyst and the substrate. In addition, the carbide pre-plating layer introduced by the present invention can optimize the inherent electronic structure of the noble metal or its oxide catalyst, thereby improving its intrinsic activity, thereby significantly reducing the loading amount of the noble metal element.
[0026] The present invention provides a method for preparing a catalyst diffusion electrode as described in the above technical solution, firstly, a carbide pre-plating layer is coated on the surface of the diffusion material by vapor deposition, and then a catalyst is prepared on the surface of the diffusion material covered with the carbide pre-plating layer by electrochemical deposition. The preparation methods of traditional catalyst coated electrodes, such as spraying and coating methods, must use a binder, which is a macro-scale physical bonding material forming method, while the vapor deposition method and electrochemical deposition method used in the present invention are a micro-scale in-situ growth material forming method, which is conducive to promoting atomic-scale chemical bonding between the catalyst and the substrate, thereby forming a strong interaction interface and regulating the loading amount of precious metal elements on the substrate surface, and is very suitable for the preparation of electrode materials for PEM water electrolysis.
[0027] The catalyst diffusion electrode provided by the present invention is used as a PEM water electrolysis electrode material. Compared with the traditional catalyst coated electrode, the leaching rate of the precious metal elements under long-term constant current density can be reduced by 3% to 10%, indicating that the catalyst diffusion electrode provided by the present invention has a higher bonding strength between the internal catalyst and the substrate. In addition, the catalyst diffusion electrode provided by the present invention is used as a PEM water electrolysis electrode material. Compared with the traditional catalyst coated electrode, the loading amount of precious metal elements required to achieve the same polarization curve performance is significantly reduced, indicating that the catalyst diffusion electrode provided by the present invention has a lower loading amount of precious metal elements. The present invention is conducive to promoting the industrialization of PEM electrolyzers. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a physical picture of the powder sintered titanium plate.
[0029] Figure 2 This is a SEM image of the powder sintered titanium plate at a scale of 20 μm.
[0030] Figure 3This is a SEM image of MPTP-MoC\IrO2 prepared in Example 1 of the present invention at a scale of 1 μm.
[0031] Figure 4 In the figure, a is a bar graph of the leaching amount of precious metal elements of MPTP-MoC\IrO2 prepared in Example 1 of the present invention and PEM\IrO2 prepared in Comparative Example 1, and b is a polarization curve graph of the current density-cell voltage relationship of MPTP-MoC\IrO2 prepared in Example 1 and PEM\IrO2 prepared in Comparative Example 1.
[0032] Figure 5 This is a SEM image of MPTP-MoC\IrO2 prepared in Example 2 of the present invention at a scale of 1 μm.
[0033] Figure 6 In the figure, a is a bar graph of the leaching amount of precious metal elements of MPTP-MoC\IrO2 prepared in Example 2 and PEM\IrO2 prepared in Comparative Example 2, and b is a polarization curve graph of the current density-cell voltage relationship of MPTP-MoC\IrO2 prepared in Example 2 and PEM\IrO2 prepared in Comparative Example 2.
[0034] Figure 7 This is a SEM image of MPTP-MoC\IrO2 prepared in Example 3 of the present invention at a scale of 1 μm.
[0035] Figure 8 In the figure, a is a bar graph of the leaching amount of precious metal elements of MPTP-MoC\IrO2 prepared in Example 3 and PEM\IrO2 prepared in Comparative Example 3, and b is a polarization curve graph of the current density-cell voltage relationship of MPTP-MoC\IrO2 prepared in Example 3 and PEM\IrO2 prepared in Comparative Example 3. DETAILED DESCRIPTION
[0036] In order to enable those skilled in the art to better understand the technical solution of the present invention and implement it, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention. The experimental methods and detection methods described in the following embodiments are conventional methods unless otherwise specified; the reagents and materials described are all commercially available unless otherwise specified.
[0037] The present invention provides a catalyst diffusion electrode, comprising a diffusion material, a carbide pre-plating layer is deposited on the surface of the diffusion material, and a noble metal or its oxide catalyst is deposited on the surface of the carbide pre-plating layer.
[0038] The catalyst diffusion electrode provided by the present invention includes a diffusion material. In the present invention, the diffusion material is preferably one or more of fiber sintered titanium felt and powder sintered titanium plate, and more preferably a powder sintered titanium plate; the thickness of the diffusion material is preferably 0.1 mm to 2.0 mm, and more preferably 0.1 mm to 0.8 mm; the porosity of the diffusion material is preferably 20% to 80%, and more preferably 50% to 80%; the average particle size of the diffusion material is preferably 1 μm to 100 μm, and more preferably 1 μm to 50 μm.
[0039] The catalyst diffusion electrode provided by the present invention comprises a carbide pre-plating layer arranged on the surface of the diffusion material. In the present invention, the carbide pre-plating layer is preferably one or more of MoC, Mo2C, WC and W2C, more preferably MoC and Mo2C; the carbide pre-plating layer is in the form of a thin film, and the thickness is preferably 1 μm to 10 μm, more preferably 1 μm to 5 μm.
[0040] The catalyst diffusion electrode provided by the present invention comprises a noble metal or its oxide catalyst disposed on the surface of a carbide pre-plating layer. In the present invention, the noble metal or its oxide catalyst is preferably one or more of Pt, Ir, Ru, PtO, PtO2, IrO2, IrO3, Ir2O3, RuO2 and RuO4, more preferably Pt, IrO2; the noble metal or its oxide catalyst is in granular form, with a particle size of 1nm to 10nm, more preferably 1nm to 5nm.
[0041] In the present invention, the coverage of the noble metal or its oxide catalyst on the surface of the carbide pre-plating layer is preferably 50% to 100%, more preferably 60% to 90%; the mass ratio of the noble metal or its oxide catalyst to the carbide pre-plating layer is preferably 1% to 10%, more preferably 1% to 5%.
[0042] The present invention provides a method for preparing the catalyst diffusion electrode described in the above technical solution, comprising the following steps:
[0043] (1) A carbide pre-coating is prepared on the surface of the diffusion material by vapor deposition.
[0044] (2) Precious metal or its oxide catalyst is prepared on the surface of a diffusion material covered with a carbide pre-plating layer by electrochemical deposition.
[0045] The present invention adopts a vapor deposition method to prepare a carbide pre-plating layer on the surface of the diffusion material. Before preparing the carbide pre-plating layer, the present invention preferably also includes pre-treatment of the diffusion material. In the present invention, the pre-treatment preferably includes acetone washing, ethanol washing, acid washing, water washing and drying in sequence. In the present invention, the acetone washing is preferably carried out with an acetone solution with a purity of 99wt% or more. In the present invention, the ethanol washing is preferably carried out with an ethanol solution with a purity of 99wt% or more. In the present invention, the acid washing solution is preferably a hydrochloric acid aqueous solution, and the hydrogen ion concentration is preferably 0.1mol / L. In the present invention, the water washing is preferably deionized water washing. In the present invention, the acetone washing, ethanol washing, acid washing and water washing are preferably ultrasonic washing, and the time of each ultrasonic washing is preferably more than 15min, more preferably 20min. The present invention ensures that the oil, impurities and oxide layer on the surface of the diffusion material are completely removed by carrying out acetone washing, ethanol washing, acid washing and water washing in sequence. In the present invention, the drying is preferably air-dried at room temperature.
[0046] In the present invention, the vapor deposition method is preferably one or more of physical vapor deposition and chemical vapor deposition, and more preferably physical vapor deposition. In the present invention, the carbide pre-plating layer is prepared on the surface of the diffusion material by using the vapor deposition method, including: using carbide as a source material, using the diffusion material as a substrate, controlling the vacuum degree and temperature of the chamber, and applying power to prepare the carbide pre-plating layer on the surface of the diffusion material.
[0047] In the present invention, the purity of the carbide source material is preferably above 99%. In the present invention, the vacuum degree of the chamber is preferably 8.0×10 -4 Pa or less, more preferably 5×10 -4 Pa or less; the chamber temperature is preferably 100°C to 500°C, more preferably 100°C to 300°C. In the present invention, the power of the power source is preferably 100W to 500W, more preferably 200W to 300W, and the application time of the power source is preferably 200s to 1000s, more preferably 400s to 800s.
[0048] In the present invention, the electrochemical deposition method is preferably one or more of an anodic oxidation method and a cathodic reduction method, and more preferably an anodic oxidation method. In the present invention, the electrochemical deposition method is used to prepare a noble metal or its oxide catalyst on the surface of a diffusion material covered with a carbide pre-plating layer, comprising: using a diffusion material covered with a carbide pre-plating layer as a working electrode, using an aqueous solution of a noble metal salt, a complexing agent and a pH regulator as an electrolyte solution, applying a redox potential to prepare a noble metal or its oxide catalyst on the surface of a diffusion material covered with a carbide pre-plating layer.
[0049] In the present invention, the precious metal salt is preferably one or more of platinum salt, iridium salt, and ruthenium salt, more preferably platinum salt and iridium salt. In the present invention, the complexing agent is preferably oxalic acid and oxalate, more preferably oxalic acid. In the present invention, the role of the complexing agent is to maintain the precious metal in the electrolyte in an ionic state. In the present invention, the pH regulator is preferably potassium carbonate and sodium hydroxide, more preferably potassium carbonate. In the present invention, the role of the pH regulator is to regulate the acid-base environment of the electrolyte solution. In the present invention, the concentration of the precious metal salt in the electrolyte solution is preferably 1mmol / L to 10mmol / L, more preferably 1mmol / L to 5mmol / L. In the present invention, the concentration of the complexing agent in the electrolyte solution is preferably 10mmol / L to 100mmol / L, more preferably 10mmol / L to 50mmol / L. In the present invention, the pH value of the electrolyte solution is preferably 9 to 12, more preferably 10 to 11. In the present invention, the oxidation-reduction potential range is preferably -1.2 to 1.0 V vs SCE, more preferably -1.0 to 0.8 V vs SCE; the oxidation-reduction potential time is preferably 20 min to 100 min, more preferably 40 min to 80 min. In the present invention, the electrochemical deposition method is carried out in a three-electrode system using a cyclic voltammetry mode, the counter electrode is a Pt sheet, and the reference electrode is SCE.
[0050] The present invention provides the use of the catalyst diffusion electrode described in the above technical solution or the catalyst diffusion electrode prepared by the preparation method described in the above technical solution in PEM water electrolysis electrode materials, preferably used in PEM water electrolysis anode side electrode materials.
[0051] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0052] Before describing the embodiments, the powder sintered titanium plate (ie, diffusion material) and the powder sintered titanium plate covered with a molybdenum carbide pre-plating layer involved in the embodiments are described below. Figure 1 This is a physical picture of the powder sintered titanium plate, with a thickness of approximately 0.4mm. Figure 2 This is the SEM image of the powder sintered titanium plate at a scale of 20μm. It can be seen that the powder sintered titanium plate is sintered from powder particles of different sizes, with an average particle size of about 30μm. There are holes of different sizes evenly distributed in the material, and the porosity is about 60%.
[0053] Example 1
[0054] The preparation method of the catalyst diffusion electrode (MPTP-MoC\IrO2) comprises the following steps:
[0055] Pretreatment of diffusion material: First cut the area into 5*5cm 2 The MPTP was then ultrasonically cleaned in 99.9 wt% acetone solution, 99.9 wt% ethanol solution, 0.1 mol / L hydrochloric acid solution and deionized water for 20 min, and finally fully air-dried at room temperature to obtain the pretreated MPTP.
[0056] Preparation of MoC pre-plating: MoC with a purity of 99.9% was used as the target material, and pre-treated MPTP was used as the substrate. The vacuum degree of the chamber was controlled at 4×10 -4 Pa, the chamber temperature was 200°C, and the power supply was set to 200 W for 600 s of physical vapor deposition to obtain MPTP covered with a MoC pre-plating layer (MPTP-MoC).
[0057] Preparation of precious metal oxide catalysts: An aqueous solution containing 3 mmol / L IrCl3 and 30 mmol / L H2C2O4 was prepared as an electrolyte solution in an electrolytic cell, and K2CO3 was continuously added thereto to adjust the pH of the electrolyte solution to 10.2. MPTP covered with a MoC pre-plating layer was used as the working electrode, a Pt sheet of the same size was used as the counter electrode, and SCE was used as the reference electrode. The cyclic voltammetry mode was used to continuously scan the redox potential range of 0.4 to 0.8 V vs SCE for 60 min to obtain a catalyst diffusion electrode (MPTP-MoC\IrO2).
[0058] Comparative Example 1
[0059] The preparation method of the catalyst coated electrode (PEM\IrO2) comprises the following steps:
[0060] Pre-processing of PEM: First cut the area into 5*5cm 2 The PEM was then ultrasonically cleaned in deionized water for 20 minutes, and finally fully air-dried at room temperature to obtain the pretreated PEM.
[0061] Preparation of precious metal oxide catalyst: 500 mg of IrO2 catalyst was placed in 1 L of mixed solution (containing 980 mL of ethanol and 20 mL of 5 wt% Nafion), ultrasonically oscillated for 120 min, and the formed catalyst slurry was evenly sprayed on one side of the pretreated PEM using a spray gun for 10 min to obtain a catalyst-coated electrode (PEM\IrO2).
[0062] The SEM image of the catalyst diffusion electrode MPTP-MoC\IrO2 prepared in Example 1 is as follows Figure 3 As shown, it can be seen that the surface of MPTP is covered with a thin film of MoC pre-plating layer with a thickness of about 3μm, and on the MoC pre-plating layer, uniformly distributed granular IrO2 catalyst with a particle size of about 3nm. In addition, the coverage rate of IrO2 catalyst on the surface of MoC pre-plating layer is about 80%, and the mass ratio of IrO2 catalyst to MoC pre-plating layer is about 2.0%. The loading amount of precious metal element Ir in the catalyst diffusion electrode MPTP-MoC\IrO2 prepared in Example 1 is about 0.10mg / cm 2 .
[0063] The loading amount of the precious metal element Ir in the catalyst-coated electrode PEM\IrO2 prepared in Comparative Example 1 is about 1.0 mg / cm 2 .
[0064] Figure 4 In FIG. 1 , a is a bar graph of the leaching amount of precious metal elements of MPTP-MoC\IrO2 prepared in Example 1 and PEM\IrO2 prepared in Comparative Example 1. Compared with PEM\IrO2 (leaching rate is 10.0%), the leaching rate of precious metal elements of MPTP-MoC\IrO2 at a constant current density of 600h (specifically 3.7%) can be reduced by 6.3%. Figure 4 b is the polarization curve of the MPTP-MoC\IrO2 prepared in Example 1 and the PEM\IrO2 prepared in Comparative Example 1 about the relationship between current density and cell voltage. It can be seen that compared with PEM\IrO2 (Ir loading is about 1.0 mg / cm 2 ), the required precious metal content (0.10 mg / cm 2 ) can be reduced by 90%.
[0065] Example 2
[0066] The preparation method of the catalyst diffusion electrode (MPTP-MoC\IrO2) comprises the following steps:
[0067] Pretreatment of diffusion material: First cut the area into 5*5cm 2 The MPTP was then ultrasonically cleaned in 99.9 wt% acetone solution, 99.9 wt% ethanol solution, 0.1 mol / L hydrochloric acid solution and deionized water for 20 min, and finally fully air-dried at room temperature to obtain the pretreated MPTP.
[0068] Preparation of MoC pre-plating: MoC with a purity of 99.9% was used as the target material, and pre-treated MPTP was used as the substrate. The vacuum degree of the chamber was controlled at 4×10 -4 Pa, the chamber temperature was 200°C, and the power supply was set to 200 W for 600 s of physical vapor deposition to obtain MPTP covered with a MoC pre-plating layer (MPTP-MoC).
[0069] Preparation of precious metal oxide catalysts: An aqueous solution containing 3mmol / L IrCl3 and 30mmol / L H2C2O4 was prepared as an electrolyte solution in an electrolytic cell, and K2CO3 was continuously added thereto to adjust the pH of the electrolyte solution to 10.2. MPTP covered with a MoC pre-plating layer was used as the working electrode, a Pt sheet of the same size was used as the counter electrode, and SCE was used as the reference electrode. The cyclic voltammetry mode was used to continuously scan the redox potential range of 0.4-0.8V vs SCE for 80min to obtain a catalyst diffusion electrode (MPTP-MoC\IrO2).
[0070] Comparative Example 2
[0071] The preparation method of the catalyst coated electrode (PEM\IrO2) comprises the following steps:
[0072] Pre-processing of PEM: First cut the area into 5*5cm 2 The PEM was then ultrasonically cleaned in deionized water for 20 minutes, and finally fully air-dried at room temperature to obtain the pretreated PEM.
[0073] Preparation of precious metal oxide catalyst: 500 mg of IrO2 catalyst was placed in 1 L of mixed solution (containing 980 mL of ethanol and 20 mL of 5 wt% Nafion), ultrasonically oscillated for 120 min, and the formed catalyst slurry was evenly sprayed on one side of the pretreated PEM using a spray gun for 8 min to obtain a catalyst-coated electrode (PEM\IrO2).
[0074] The SEM image of the catalyst diffusion electrode MPTP-MoC\IrO2 prepared in Example 2 is as follows Figure 5 As shown, it can be seen that the surface of MPTP is covered with a thin film of MoC pre-plating layer with a thickness of about 3μm, and on the MoC pre-plating layer, uniformly distributed granular IrO2 catalyst with a particle size of about 3nm. In addition, the coverage rate of IrO2 catalyst on the surface of MoC pre-plating layer is about 90%, and the mass ratio of IrO2 catalyst to MoC pre-plating layer is about 2.3%. The loading amount of precious metal element Ir in the catalyst diffusion electrode MPTP-MoC\IrO2 prepared in Example 2 is about 0.14mg / cm 2 .
[0075] The loading amount of precious metal element Ir in the catalyst membrane electrode PEM\IrO2 prepared in comparative example 2 is about 0.8 mg / cm 2 .
[0076] Figure 6 In FIG. 1 , a is a bar graph of the leaching amount of precious metal elements of MPTP-MoC\IrO2 prepared in Example 2 and PEM\IrO2 prepared in Comparative Example 2. Compared with PEM\IrO2 (leaching rate is 10.0%), the leaching rate of precious metal elements (4.2%) of MPTP-MoC\IrO2 at a constant current density of 600h can be reduced by 5.8%. Figure 6 b is the polarization curve of the MPTP-MoC\IrO2 prepared in Example 2 and the PEM\IrO2 prepared in Comparative Example 2 about the relationship between current density and cell voltage. It can be seen that compared with PEM\IrO2 (Ir loading is about 0.8 mg / cm 2 ), the required precious metal content (0.14 mg / cm 2 ) can be reduced by 83%.
[0077] Example 3
[0078] The preparation method of the catalyst diffusion electrode (MPTP-MoC\IrO2) comprises the following steps:
[0079] Pretreatment of diffusion material: First cut the area into 5*5cm 2 The MPTP was then ultrasonically cleaned in 99.9 wt% acetone solution, 99.9 wt% ethanol solution, 0.1 mol / L hydrochloric acid solution and deionized water for 20 min, and finally fully air-dried at room temperature to obtain the pretreated MPTP.
[0080] Preparation of MoC pre-plating: MoC with a purity of 99.9% was used as the target material, and pre-treated MPTP was used as the substrate. The vacuum degree of the chamber was controlled at 4×10 -4 Pa, the chamber temperature was 200°C, and the power supply was set to 200 W for 600 s of physical vapor deposition to obtain MPTP covered with a MoC pre-plating layer (MPTP-MoC).
[0081] Preparation of precious metal oxide catalysts: An aqueous solution containing 3mmol / L IrCl3 and 30mmol / L H2C2O4 was prepared as an electrolyte solution in an electrolytic cell, and K2CO3 was continuously added thereto to adjust the pH of the electrolyte solution to 10.2. MPTP covered with a MoC pre-plating layer was used as the working electrode, a Pt sheet of the same area was used as the counter electrode, and SCE was used as the reference electrode. The cyclic voltammetry mode was used to continuously scan the redox potential range of 0.4-0.8V vs SCE for 40min to obtain a catalyst diffusion electrode (MPTP-MoC\IrO2).
[0082] Comparative Example 3
[0083] The preparation method of the catalyst coated electrode (PEM\IrO2) comprises the following steps:
[0084] Pre-processing of PEM: First cut the area into 5*5cm 2 The PEM was then ultrasonically cleaned in deionized water for 20 minutes, and finally fully air-dried at room temperature to obtain the pretreated PEM.
[0085] Preparation of precious metal oxide catalyst: 500 mg of IrO2 catalyst was placed in 1 L of mixed solution (containing 980 mL of ethanol and 20 mL of 5 wt% Nafion), ultrasonically oscillated for 120 min, and the formed catalyst slurry was evenly sprayed on one side of the pretreated PEM using a spray gun for 5 min to obtain a catalyst-coated electrode (PEM\IrO2).
[0086] The SEM image of the catalyst diffusion electrode MPTP-MoC\IrO2 prepared in Example 3 is as follows Figure 7 As shown, it can be seen that the surface of MPTP is covered with a thin film of MoC pre-plating layer with a thickness of about 3μm, and on the MoC pre-plating layer, uniformly distributed granular IrO2 catalyst with a particle size of about 3nm. In addition, the coverage rate of IrO2 catalyst on the surface of MoC pre-plating layer is about 60%, and the mass ratio of IrO2 catalyst to MoC pre-plating layer is about 1.5%. The loading amount of precious metal element Ir in the catalyst diffusion electrode MPTP-MoC\IrO2 prepared in Example 3 is about 0.06mg / cm 2 .
[0087] The loading amount of precious metal element Ir in the catalyst membrane electrode PEM\IrO2 prepared in comparative example 3 is about 0.6 mg / cm 2 .
[0088] Figure 8In FIG. 1 , a is a bar graph of the leaching amount of precious metal elements of MPTP-MoC\IrO2 prepared in Example 3 and PEM\IrO2 prepared in Comparative Example 3. Compared with PEM\IrO2 (leaching rate is 10.0%), the leaching rate of precious metal elements (3.1%) of MPTP-MoC\IrO2 at a constant current density of 600h can be reduced by 6.9%. Figure 8 b is the polarization curve of the MPTP-MoC\IrO2 prepared in Example 3 and the PEM\IrO2 prepared in Comparative Example 3 about the relationship between current density and cell voltage. It can be seen that compared with PEM\IrO2 (Ir loading is about 0.6 mg / cm 2 ), the required precious metal content (0.06 mg / cm 2 ) can be reduced by 90%.
[0089] Example 4
[0090] The preparation method of the catalyst diffusion electrode (MPTP-WC\IrO2) comprises the following steps:
[0091] Pretreatment of diffusion material: First cut the area into 5*5cm 2 The MPTP was then ultrasonically cleaned in 99.9 wt% acetone solution, 99.9 wt% ethanol solution, 0.1 mol / L hydrochloric acid solution and deionized water for 20 min, and finally fully air-dried at room temperature to obtain the pretreated MPTP.
[0092] Preparation of tungsten carbide pre-plating: WC with a purity of 99.9% was used as the target material, and pre-treated MPTP was used as the substrate. The vacuum degree of the chamber was controlled at 4×10 -4 Pa, the chamber temperature was 200°C, and the power supply was set to 300 W for 600 s of physical vapor deposition to obtain MPTP covered with a WC pre-plating layer (MPTP-WC).
[0093] Preparation of precious metal oxide catalysts: An aqueous solution containing 3mmol / L IrCl3 and 30mmol / L H2C2O4 was prepared as an electrolyte solution in an electrolytic cell, and K2CO3 was continuously added thereto to adjust the pH of the electrolyte solution to 10.2. MPTP covered with a WC pre-plating layer was used as the working electrode, a Pt sheet of the same size was used as the counter electrode, and SCE was used as the reference electrode. The cyclic voltammetry mode was used to continuously scan the redox potential range of 0.4-0.8V vs SCE for 30min to obtain a catalyst diffusion electrode (MPTP-WC\IrO2).
[0094] Comparative Example 4
[0095] The preparation method of the catalyst coated electrode (PEM\IrO2) comprises the following steps:
[0096] Pre-processing of PEM: First cut the area into 5*5cm 2 The PEM was then ultrasonically cleaned in deionized water for 20 minutes, and finally fully air-dried at room temperature to obtain the pretreated PEM.
[0097] Preparation of precious metal oxide catalyst: 500 mg of IrO2 catalyst was placed in 1 L of mixed solution (containing 980 mL of ethanol and 20 mL of 5 wt% Nafion), ultrasonically oscillated for 120 min, and the formed catalyst slurry was evenly sprayed on one side of the pretreated PEM using a spray gun for 2 min to obtain a catalyst-coated electrode (PEM\IrO2).
[0098] In the catalyst diffusion electrode MPTP-WC\IrO2 prepared in Example 4, the thickness of the WC pre-plating layer is about 3μm, and the particle size of the IrO2 catalyst is about 3nm. In addition, the coverage of the IrO2 catalyst on the surface of the WC pre-plating layer is about 50%, and the mass ratio of the IrO2 catalyst to the WC pre-plating layer is about 1.0%. The loading amount of the precious metal element Ir in the catalyst diffusion electrode MPTP-WC\IrO2 prepared in Example 4 is about 0.02mg / cm 2 .
[0099] The loading amount of precious metal element Ir in the catalyst membrane electrode PEM\IrO2 prepared in comparative example 4 is about 0.2 mg / cm 2 .
[0100] The results of the leaching of precious metal elements from MPTP-WC\IrO2 prepared in Example 4 and PEM\IrO2 prepared in Comparative Example 4 are as follows: Compared with PEM\IrO2 (leaching rate is 10.0%), the leaching rate of precious metal elements (4.0%) of MPTP-WC\IrO2 at a constant current density of 600h can be reduced by 6.0%. The polarization curves of the MPTP-WC\IrO2 prepared in Example 4 and PEM\IrO2 prepared in Comparative Example 4 about the relationship between current density and cell voltage are as follows: Compared with PEM\IrO2 (Ir loading is about 0.2mg / cm 2 ), the precious metal content required for MPTP-MoC\IrO2 to achieve the same polarization curve performance (0.02mg / cm 2 ) can be reduced by 90%.
[0101] Example 5
[0102] The preparation method of the catalyst diffusion electrode (MPTP-Mo2C\IrO2) comprises the following steps:
[0103] Pretreatment of diffusion material: First cut the area into 5*5cm 2 The MPTP was then ultrasonically cleaned in 99.9 wt% acetone solution, 99.9 wt% ethanol solution, 0.1 mol / L hydrochloric acid solution and deionized water for 20 min, and finally fully air-dried at room temperature to obtain the pretreated MPTP.
[0104] Preparation of MoC pre-plating: Mo2C with a purity of 99.9% was used as the target material, and pre-treated MPTP was used as the substrate. The vacuum degree of the chamber was controlled at 4×10 -4 Pa, the chamber temperature was 200 °C, and the power supply was set to 200 W for 300 s of physical vapor deposition to obtain MPTP covered with a Mo2C pre-plating layer (MPTP-Mo2C).
[0105] Preparation of precious metal oxide catalysts: An aqueous solution containing 3 mmol / L IrCl3 and 30 mmol / L H2C2O4 was prepared as an electrolyte solution in an electrolytic cell, and K2CO3 was continuously added thereto to adjust the pH of the electrolyte solution to 10.2. MPTP covered with a Mo2C pre-plating layer was used as the working electrode, a Pt sheet of the same size was used as the counter electrode, and SCE was used as the reference electrode. The cyclic voltammetry mode was used to continuously scan the redox potential range of 0.4 to 0.8 V vs SCE for 100 min to obtain a catalyst diffusion electrode (MPTP-Mo2C\IrO2).
[0106] Comparative Example 5
[0107] The preparation method of the catalyst coated electrode (PEM\IrO2) comprises the following steps:
[0108] Pre-processing of PEM: First cut the area into 5*5cm 2 The PEM was then ultrasonically cleaned in deionized water for 20 minutes, and finally fully air-dried at room temperature to obtain the pretreated PEM.
[0109] Preparation of precious metal oxide catalyst: 500 mg of IrO2 catalyst was placed in 1 L of mixed solution (containing 980 mL of ethanol and 20 mL of 5 wt% Nafion), ultrasonically oscillated for 120 min, and the formed catalyst slurry was evenly sprayed on one side of the pretreated PEM using a spray gun for 3 min to obtain a catalyst-coated electrode (PEM\IrO2).
[0110] In the catalyst diffusion electrode MPTP-Mo2C\IrO2 prepared in Example 5, the thickness of the Mo2C pre-plating layer is about 1μm, and the particle size of the IrO2 catalyst is about 3nm. In addition, the coverage of the IrO2 catalyst on the surface of the Mo2C pre-plating layer is about 100%, and the mass ratio of the IrO2 catalyst to the Mo2C pre-plating layer is about 10%. The loading amount of the precious metal element Ir in the catalyst diffusion electrode MPTP-Mo2C\IrO2 prepared in Example 4 is about 0.2mg / cm 2 .
[0111] The loading amount of the precious metal element Ir in the catalyst membrane electrode PEM\IrO2 prepared in Comparative Example 5 is about 0.3 mg / cm 2 .
[0112] The results of the leaching amount of precious metal elements of MPTP-Mo2C\IrO2 prepared in Example 5 and PEM\IrO2 prepared in Comparative Example 5 are as follows: Compared with PEM\IrO2 (leaching rate is 10.0%), the leaching rate of precious metal elements (4.6%) of MPTP-Mo2C\IrO2 at a constant current density of 600h can be reduced by 5.4%. The polarization curve results of the current density-cell voltage relationship of MPTP-Mo2C\IrO2 prepared in Example 5 and PEM\IrO2 prepared in Comparative Example 5 are as follows: Compared with PEM\IrO2 (Ir loading is about 0.3mg / cm 2 ), the precious metal content required for MPTP-Mo2C\IrO2 to achieve the same polarization curve performance (0.2mg / cm 2 ) can be reduced by 33%.
[0113] Example 6
[0114] The preparation method of the catalyst diffusion electrode (MPTP-W2C\IrO2) comprises the following steps:
[0115] Pretreatment of diffusion material: First cut the area into 5*5cm 2 The MPTP was then ultrasonically cleaned in 99.9 wt% acetone solution, 99.9 wt% ethanol solution, 0.1 mol / L hydrochloric acid solution and deionized water for 20 min, and finally fully air-dried at room temperature to obtain the pretreated MPTP.
[0116] Preparation of tungsten carbide pre-plating: W2C with a purity of 99.9% was used as the target material, and pre-treated MPTP was used as the substrate. The vacuum degree of the chamber was controlled at 4×10 -4Pa, the chamber temperature was 200°C, and the power supply was set to 300 W for 300 s of physical vapor deposition to obtain MPTP covered with a W2C pre-plating layer (MPTP-W2C).
[0117] Preparation of precious metal oxide catalysts: An aqueous solution containing 3 mmol / L IrCl3 and 30 mmol / L H2C2O4 was prepared as an electrolyte solution in an electrolytic cell, and K2CO3 was continuously added thereto to adjust the pH of the electrolyte solution to 10.2. MPTP covered with a W2C pre-plating layer was used as the working electrode, a Pt sheet of the same size was used as the counter electrode, and SCE was used as the reference electrode. The cyclic voltammetry mode was used to continuously scan the redox potential range of 0.4 to 0.8 V vs SCE for 100 min to obtain a catalyst diffusion electrode (MPTP-W2C\IrO2).
[0118] Comparative Example 6
[0119] The preparation method of the catalyst coated electrode (PEM\IrO2) comprises the following steps:
[0120] Pre-processing of PEM: First cut the area into 5*5cm 2 The PEM was then ultrasonically cleaned in deionized water for 20 minutes, and finally fully air-dried at room temperature to obtain the pretreated PEM.
[0121] Preparation of precious metal oxide catalyst: 500 mg of IrO2 catalyst was placed in 1 L of mixed solution (containing 980 mL of ethanol and 20 mL of 5 wt% Nafion), ultrasonically oscillated for 120 min, and the formed catalyst slurry was evenly sprayed on one side of the pretreated PEM using a spray gun for 3 min to obtain a catalyst-coated electrode (PEM\IrO2).
[0122] In the catalyst diffusion electrode MPTP-W2C\IrO2 prepared in Example 6, the thickness of the W2C pre-plating layer is about 1μm, and the particle size of the IrO2 catalyst is about 3nm. In addition, the coverage of the IrO2 catalyst on the surface of the W2C pre-plating layer is about 100%, and the mass ratio of the IrO2 catalyst to the W2C pre-plating layer is about 6%. The loading amount of the precious metal element Ir in the catalyst diffusion electrode MPTP-W2C\IrO2 prepared in Example 6 is about 0.2mg / cm 2 .
[0123] The loading amount of precious metal element Ir in the catalyst membrane electrode PEM\IrO2 prepared in comparative example 6 is about 0.3 mg / cm 2 .
[0124] The results of the leaching amount of precious metal elements of MPTP-W2C\IrO2 prepared in Example 6 and PEM\IrO2 prepared in Comparative Example 6 are as follows: Compared with PEM\IrO2 (leaching rate is 10.0%), the leaching rate of precious metal elements (4.8%) of MPTP-W2C\IrO2 at a constant current density of 600h can be reduced by 5.2%. The polarization curve results of the current density-cell voltage relationship of MPTP-W2C\IrO2 prepared in Example 6 and PEM\IrO2 prepared in Comparative Example 6 are as follows: Compared with PEM\IrO2 (Ir loading is about 0.3mg / cm 2 ), the required precious metal content (0.2mg / cm 2 ) can be reduced by 33%.
[0125] It can be proved by the above embodiments and comparative examples that, compared with the traditional catalyst coated electrode, the catalyst diffusion electrode prepared by the present invention significantly reduces the leaching rate of precious metal elements, and the precious metal element loading required to achieve the same polarization curve performance is significantly reduced. This is because the present invention covers a layer of carbide pre-plating layer on the surface of the diffusion material as a binding site for the precious metal or its oxide catalyst. When the precious metal or its oxide catalyst lands on the surface of the diffusion material, it will be anchored together with the carbide pre-plating layer on the surface of the diffusion material (a micro-scale in-situ growth material forming method). This combination method is different from the combination method of the traditional catalyst coated electrode relying on the bonding of the binder (macro-scale physical bonding material forming method), which is a strong interaction force, which can significantly enhance the bonding strength between the catalyst and the substrate. In addition, the carbide pre-plating layer introduced by the present invention can optimize the inherent electronic structure of the precious metal or its oxide catalyst, thereby improving its intrinsic activity, thereby significantly reducing the loading of the precious metal element.
[0126] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, they are also intended to be included.
Claims
1. A catalyst diffusion electrode, characterized in that: The invention comprises a diffusion material, a carbide pre-plating layer is deposited on the surface of the diffusion material, and a noble metal or an oxide catalyst thereof is deposited on the surface of the carbide pre-plating layer.
2. The catalyst diffusion electrode according to claim 1, characterized in that: The carbide pre-plating layer is one or more of MoC, Mo2C, WC and W2C; the carbide pre-plating layer is in the form of a thin film.
3. The catalyst diffusion electrode according to claim 1, characterized in that: The noble metal or its oxide catalyst is one or more of Pt, Ir, Ru, PtO, PtO2, IrO2, IrO3, Ir2O3, RuO2 and RuO4, and the noble metal or its oxide catalyst is in granular form with a particle size of 1nm to 10nm.
4. The catalyst diffusion electrode according to claim 1, characterized in that: The coverage rate of the noble metal or its oxide catalyst on the surface of the carbide pre-plating layer is 50% to 100%; the mass ratio of the noble metal or its oxide catalyst to the carbide pre-plating layer is 1% to 10%.
5. The method for preparing a catalyst diffusion electrode according to claim 1, characterized in that: The following steps are involved: A carbide pre-plating layer is prepared on the surface of the diffusion material by using a vapor deposition method; The noble metal or its oxide catalyst is prepared on the surface of a diffusion material covered with a carbide pre-plating layer by an electrochemical deposition method.
6. The preparation method according to claim 5, characterized in that: The vapor deposition method is physical vapor deposition or chemical vapor deposition.
7. The preparation method according to claim 5, characterized in that: The method for preparing a carbide pre-plating layer comprises the following steps: using carbide as a source material, using a diffusion material as a substrate, controlling the vacuum degree and temperature of a chamber, and applying power to prepare a carbide pre-plating layer on the surface of the diffusion material.
8. The preparation method according to claim 5, characterized in that: The electrochemical deposition method is either anodic oxidation or cathodic reduction.
9. The preparation method according to claim 5, characterized in that: The noble metal or its oxide catalyst is deposited on the surface of the carbide pre-plating layer by the following steps: using a diffusion material covered with a carbide pre-plating layer as a working electrode, using an aqueous solution of a noble metal salt, a complexing agent and a pH regulator as an electrolyte solution, applying a redox potential, and preparing the noble metal or its oxide catalyst on the surface of the diffusion material covered with the carbide pre-plating layer.
10. Use of the catalyst diffusion electrode according to claim 1 in proton exchange membrane water electrolysis electrode materials.